Internship Reports and Monograph titled: "Inkjet Printing: A novel approach for manufacturing personalized medicines" - Vale, Alexandra Manso Machado (2018)
Relatório de Estágio do Mestrado Integrado em Ciências Farmacêuticas apresentado à Faculdade de Farmácia